2020
DOI: 10.1002/hep4.1497
|View full text |Cite
|
Sign up to set email alerts
|

Integrated GWAS and mRNA Microarray Analysis Identified IFNG and CD40L as the Central Upstream Regulators in Primary Biliary Cholangitis

Abstract: Genome-wide association studies (GWASs) in European and East Asian populations have identified more than 40 disease-susceptibility genes in primary biliary cholangitis (PBC). The aim of this study is to computationally identify disease pathways, upstream regulators, and therapeutic targets in PBC through integrated GWAS and messenger RNA (mRNA) microarray analysis. Disease pathways and upstream regulators were analyzed with ingenuity pathway analysis in data set 1 for GWASs (1,920 patients with PBC and 1,770 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, one variant in the channel's ß subunit (KCNMB1) has been repeatedly shown to exert a protective effect against cardiovascular disease [89][90][91][92][93][94]. KCNMA1 has also been implicated in inflammatory pathology, including angioedema in response to specific antihypertensives [95], chronic rhinosinusitis [96], and primary biliary cholangitis [97]. GWAS has further uncovered KCNMA1-linked variations in drug and nutrient metabolism, including selenium [98], thiopurine chemotherapy [99,100], and ranibizumab for age-related macular degeneration [101].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…Interestingly, one variant in the channel's ß subunit (KCNMB1) has been repeatedly shown to exert a protective effect against cardiovascular disease [89][90][91][92][93][94]. KCNMA1 has also been implicated in inflammatory pathology, including angioedema in response to specific antihypertensives [95], chronic rhinosinusitis [96], and primary biliary cholangitis [97]. GWAS has further uncovered KCNMA1-linked variations in drug and nutrient metabolism, including selenium [98], thiopurine chemotherapy [99,100], and ranibizumab for age-related macular degeneration [101].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…Accumulating evidences suggest that IFN pathways may participate in the pathogenesis of PBC 20 24 , however, there has been no report regarding IFIT3 in PBC to our knowledge. Recent integrated analysis using GWAS, and mRNA microarray data sets predicted that IFNG and CD40L are the central upstream regulators in both disease susceptibility and activity of PBC 24 . The interplay of types I and II IFN is also implicated as a cause of human PBC 23 and a murine model of autoimmune cholangitis 22 .…”
Section: Discussionmentioning
confidence: 90%
“…IFIT3 is an IFN-induced antiviral protein acting as an inhibitor of cellular and viral processes, cell migration, proliferation, signaling, and viral replication 17 19 . A participation of IFN pathways in the pathogenesis of PBC was previously reported 20 24 , so we selected IFIT3 for further examination.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the high levels of IgM and its role in PBC remains unclear. Genomic and miRNA analyses have indicated that IFNγ and CD40L are central upstream regulators of PBC ( 132 ). One study also found that reduced methylation of the CD40L promoter in CD4 + T cells was inversely associated with IgM levels in PBC ( 133 ).…”
Section: Regulation Of Immune Response Abnormality By Ppars In Pbcmentioning
confidence: 99%